Antioxidant Vitamins and Carotenoids Intake and the Association With Poor Semen Quality: A Cross-Sectional Analysis of Men Referring to an Italian Fertility Clinic - De Cosmi, Valentina; Parazzini, Fabio; Agostoni, Carlo; Noli, Stefania; Cipriani, Sonia; La Vecchia, Irene; Ferrari, Stefania; Esposito, Giovanna; Bravi, Francesca; Ricci, Elena (Frontiers in Nutrition, 2021)
Several studies suggested that male’s diet affects fertility. This cross-sectional analysis from a prospective cohort study aims to explore the relation between antioxidants intake and sperm parameters in sub-fertile couples re-ferring to a Fertility center. Socio-demographic characteristics, health history, lifestyle habits and diet information were obtained. A semen sample was analyzed to proceed with assisted reproduction. Three hundred and twenty-three men were enrolled: 19.1% had semen volume (SV) < 1.5 mL, 31.4% sperm concentration (SC) < 15.0 mil/mL, 26.8% sperm motility < 32% and 33.0% had total sperm count (TSC) < 39.0 mil. Higher levels of α-carotene were associated to lower risk of low SC (4th vs 1st quartile, adjusted OR (aOR) 0.43, 95% CI 0.20-0.91) and low TSC (aOR 0.46, 95% CI 0.22-0.95). Higher intake of β-carotene was inversely associated with risk of low TSC. Lycopene intake was associated with higher risk for these conditions (aOR 2.46, 95%CI 1.01-5.98) SC, and (aOR 3.11, 95%CI 1.29-7.50, TSC). Risk of low semen volume was lower in men with higher level of vitamin D intake (aOR 0.25, 95%CI 0.09-0.66)). Further research, especially, well-designed randomized clinical trials (RCT), is needed to understand how diet modifications may have a role in modulating male fertility and fecundability.